Clay nanosheet-mediated delivery of recombinant plasmids expressing artificial miRNAs via leaf spray to prevent infection by plant DNA viruses. (1st November 2020) - Liu, Qili; Li, Yanpeng; Xu, Kedong; Li, Dongxiao; Hu, Haiyan; Zhou, Feng; Song, Puwen; Yu, Yongang; Wei, Qichao; Liu, Qian; Wang, Weipeng; Bu, Ruifang; et al.
Abstract: Whitefly-transmitted begomoviruses are economically important plant pathogens that cause severe problems in many crop plants, such as tomato, papaya, cotton, and tobacco. Tomato yellow leaf curl virus (TYLCV) is a typical monopartite begomovirus that has been extensively studied, but methods that can efficiently control begomoviruses are still scarce. In this study, we combined artificial microRNA (amiRNA)-mediated silencing technology and clay nanosheet-mediated delivery by spraying and developed a method for efficiently preventing TYLCV infection in tomato plants. We designed three amiRNAs that target different regions of TYLCV to silence virus-produced transcripts. Three plant expression vectors expressing pre-amiRNAs were constructed, and recombinant plasmid DNAs (pDNAs) were loaded onto nontoxic and degradable layered double hydroxide (LDH) clay nanosheets. LDH nanosheets containing multiple pDNAs were sprayed onto plant leaves. We found that the designed amiRNAs were significantly accumulated in leaves 7 days after spraying, while the pDNAs were sustainably detected for 35 days after the spray, suggesting that the LDH nanosheets released pDNAs in a sustained manner, protected pDNAs from degradation and efficiently delivered pDNAs into plant cells. Importantly, when the LDH nanosheets coated with pDNAs were sprayed onto plants infected by TYLCV, both the disease severity and TYLCV viral concentration in sprayed plants were significantly decreased during the 35 days, while the levels of H2 O2 were significantly increased in those plants. Taken together, these results indicate that LDH nanosheets loaded with pDNAs expressing amiRNAs can be a sustainable and promising tool for begomovirus control.